100 Ethel bridges: can simulation be used to drive learning in the clinical environment?. (17th November 2016) - Jakeman, Nicola; Adams, N; Adhikary, R; Gayner, R; King, E; Tomsett, A; Mann, D; Hollamby, J; Warwick, B; Else, K; Hawkins, J; Barr, J
Abstract : Feedback from Bristol final year medical students suggests they gain little clinical experience in the following areas. Incident reporting Mental capacity assessment DOLs Duty of Candour Telephone conversations with family Confidentiality Breaking bad news DNAR/TEP conversations. how to broach/when to escalate Certifying Death Talking to the coroner. when, who, how? Filling out a death certificate These topics are taught as part of a spiral curriculum with many opportunities to gain practical experience on the ward. Feedback suggests students lack confidence in these areas which impacts on their willingness to seek out learning opportunities on the ward. To mitigate this gap in experience, build confidence and drive learning in the clinical environment, four scenarios were developed. Ethel admitted with confusion and agitation secondary to pneumonia. Wants to self discharge. Management of the confused patient and capacity assessment. Ethel falls and breaks her hip. Conversation with daughter. Duty of Candour and Incident Reporting. Ethel is continuing to deteriorate and it is becoming apparent that she is dying. Face to face discussion with daughter and telephone conversation with Ethel's next door neighbour raising issues of confidentiality. Ethel has died. Certify death. Practicalities of death certification and discussion with coroner. Scenarios were piloted with 112 final year students and feedback sought from students and faculty. 1 students had gained practical experience of the areas covered in the scenarios on the ward. 105 of the 112 students reported that they would seek out similar learning opportunities on the ward. Feedback is currently being sought to ascertain whether the students subsequently sought out further learning opportunities on the ward to reinforce the simulated practice. The future: Work presented to Bristol Medical School. Simulations will replace tutorials building student confidence and driving learning in the ward.